Leading into the World - Galbreath, Paul (Rowman & Littlefield Publishers, 2014)
The call to care for creation is a central part of our discipleship as followers of Jesus Christ. However, language and imagery of the earth is often absent in our worship services. This book helps reconnect our commitment to creation care with our life of discipleship. The process includes helping congregational members name ways that they are involved in caring for creationand encouraging them to see ways that these practices are related to Christian faith, and in doing so, nurturing the life of our communities while fostering our identity as those who care for the earth. Central to the process of reconnecting holy discipleship with earth stewardship is the development and rediscovery of biblical imagery and language that will support our care of creation and shape our prayers. As our actions are more closely connected to the language of our prayers, praying and acting will inform and enrich each other. This book also includes custom liturgies that highlight earth care, prayerfully prepared for the major festivals of the church year.